Soil Quality Variation under Different Land Use Types in Haramosh Valley, Gilgit, Pakistan: Soil Quality Variation under Different Land Use Types in Haramosh Valley, Gilgit, Pakistan - Begum, Farida; Alam, Muneer; Mumtaz, Sameena; Ali, Manzoor; Zafar, Muhammad; Ali, Karamat; Hussain, Iqtidar; Khan, Akbar; Wafee, Seema (International Journal of Economic and Environmental Geology, 2019)
Soil quality is a fundamental component of environmental quality and impact of land use is also a key instigating factor in today’s rapid urbanization era. The study aims to evaluate the effects of different land-use type on selected soil quality indicators. Sixty soil samples were collected from various land use types, i.e, pasture, forest, and agriculture from a depth of 0-15cm. Analysis of variance (ANOVA) showed that the land use type significantly affected the soil’s physical and chemical properties. The moisture content was significantly higher (p<0.001) in the pasture (41.7%) than the forest (26.2%) and lowest in agricultural land (14.4%). The soil pH was significantly higher or slightly alkaline for agriculture (7.8), while for pasture (6.5) and forest (6.1), it was found to be slightly acidic. Electric conductivity (EC) and bulk density (BD) did not vary significantly with land use type, but the EC followed the decreasing order: agriculture (328.7μS/cm) > pasture (235μS/cm) > forest (203.7μS/cm). The soil organic matter (SOM) and soil organic carbon (SOC) was statistically and significantly (p<0.05) different with land use type and found in the order: forest (3.0%, 1.3 %) > pasture land (2.9%, 1.2%) > arable land (2.5%, 1.1%). NO3-N, available P and exchangeable K did not vary significantly across land use types, however, mean values were higher for agriculture (10.2mg/kg, 4.5mg/kg, 66mg/kg) than forest (10mg/kg,3.5mg/kg, 60mg/kg) and pasture (9.8mg/kg, 4.3, 60.2mg/kg). Alpine soils are good ecological indicators because of vulnerability to environmental change, therefore, regular monitoring of soil properties along with carbon stocks is essential to maintain soil health, enhance agricultural productivity and sustain agro-ecosystems.